Prawne problemy kierowania procesami gospodarczymi w Japonii - Leszczyński, Leszek (Wydział Prawa i Administracji UAM, 1991)
The article presents the functioning of a specific form of administrative guidance (gyoseishido) in Japan. Gyoseishido is a kind of formally not binding guidelines issued by the organ of (usually* state) administration, addressed to economic units (producers, tradesmen, financial institutions). Gyoseishido is to induce them to implement a certain economic policy or undertake a certain individual task. The article discusses various classifications of such guidelines. The most important of them distinguishes gyoseishido that is to regulate production and exchange, harmonise colliding interests and promote particular economic undertakings. Legal problems are centered around four issues: a) legal basis of issuing gyoseishido; b) lack of binding force of gyoseishido; c) lack of judical control over the legality of gyoseishido; d) civil liability and criminal responsibility for acts taken in connection with implementing gyoseishido, if such acts infringe the law. The Author concludes that gyoseishido is a product of cultural traits of the Japanese society, maintains those traits and introduces specific relations between politics and economy. Besides, it diminishes the role of legality, widens the sphere of administrative discretion and "softens" the concept of law by shifting the centre of gravity from formally enacted legal norm to actually functioning ones.
Legal problems of managing the economic processes in Japan